Pembangunan Karakter Aparatur Sipil Negara Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Depok - Endang Madali (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The quality of the character of the state civil apparatus (ASN) determines the effectiveness of public services. This community service aims to build the character of ASN through a training and coaching approach conducted with the Depok City Personnel and Human Resources Development Agency (BKPSDM). The activity method is in the form of training on ASN basic values (BerAKHLAK), integrity coaching, and strengthening work ethic. The results of the activity showed an increase in ASN's understanding of the values of integrity, excellent service, and responsibility. This activity is expected to become a replication model in other agencies to improve the quality of ASN character.